Kepemimpinan Kepala Sekolah dalam Pelaksanaan Manajemen Sekolah di Madrasah Aliyah Negeri Ende - Adzkiya S. Muhammad; Rasul Laba; Aloisius Harso (Yayasan Literasi Sains Indonesia, 2025)
This research aims to determine the leadership style of school principals in implementing school management at Madrasah Aliyah Negeri Ende. This research uses a qualitative case study approach. Qualitative research examines participant perspectives with interactive and flexible strategies. A case study is a method of in-depth and detailed research into a particular entity, phenomenon, or context. These entities can be individuals, groups, organizations, events, programs, or policies. The aim of this research is for researchers to understand the leadership style of the principal of Madrasah Aliyah Negeri Ende in implementing school management. Education Management is a management process in carrying out educational tasks by utilizing all resources efficiently to achieve goals effectively. School management means optimizing resources regarding school empowerment which is the most appropriate alternative for creating a school that is independent and has high excellence. Principal leadership is the principal's ability and actions to influence, mobilize and direct the resources available in the school (teachers, staff, students, parents and the environment) to achieve the educational goals that have been set. It covers various aspects, from curriculum development to creating a positive school climate. Based on the research results, it was found that the MAN Ende principal implemented a good management system and ensured that the school administration ran smoothly and efficiently, starting from financial management, staffing, to inventory.